2011
DOI: 10.3928/01477447-20111021-24
|View full text |Cite
|
Sign up to set email alerts
|

Infected Tumor Prostheses

Abstract: Infection of tumor prostheses has been a major concern because of the extensive soft tissue dissection, long operating times, and patients' immunosuppression by cancer and adjuvant treatments. Infections most often present within 2 years postoperatively, with approximately 70% of postoperative deep infections presenting within 12 months after surgery. They are typically low organism burden infections, the pathogenesis of which is related to bacteria growing in biofilms. Staphylococci are the most common pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 85 publications
(139 reference statements)
1
28
1
7
Order By: Relevance
“…PJIs have traditionally been divided into early infections, occurring within 4 weeks postoperatively (class I), those occurring between 4 weeks and 2 years postoperatively (class II), and late infections, occurring thereafter (class III) (133) (for current classification, see the website of the American Association of Orthopedic Surgeons). The last stage, showing more subtle signs of inflammation, chronic persistent postoperative pain, and implant loosening (low-grade PJIs), is more commonly associated with CoNS (134). In a retrospective cohort study conducted across 10 hospitals over a 3-year period, CoNS were isolated from 24% of culture-positive PJIs; 89% of these were methicillin-resistant strains (129).…”
Section: S Epidermidis Groupmentioning
confidence: 99%
“…PJIs have traditionally been divided into early infections, occurring within 4 weeks postoperatively (class I), those occurring between 4 weeks and 2 years postoperatively (class II), and late infections, occurring thereafter (class III) (133) (for current classification, see the website of the American Association of Orthopedic Surgeons). The last stage, showing more subtle signs of inflammation, chronic persistent postoperative pain, and implant loosening (low-grade PJIs), is more commonly associated with CoNS (134). In a retrospective cohort study conducted across 10 hospitals over a 3-year period, CoNS were isolated from 24% of culture-positive PJIs; 89% of these were methicillin-resistant strains (129).…”
Section: S Epidermidis Groupmentioning
confidence: 99%
“…We did not use muscle flaps; however, muscle transfers may be useful to reduce the risk of infection in these cases 39 . The infection rate was associated with the extent of cortical resection; it is conceivable that extensive resections require more soft-tissue dissection and take longer, thereby increasing the infection risk 40 .…”
Section: Mechanical Complications and Infectionmentioning
confidence: 99%
“…The WHO defines four histologic liposarcoma subtypes, namely, well-differentiated, myxoid, dedifferentiated, and pleomorphic [4]. Well-differentiated liposarcomas or atypical lipomatous tumors require complete excision because of the high risk of local recurrence [6]. Two recent studies both reported that these tumors have 5-year local recurrence rates of approximately 50% [7, 8].…”
Section: Discussionmentioning
confidence: 99%